GLOBECOM 2017 - 2017 IEEE Global Communications Conference 2017
DOI: 10.1109/glocom.2017.8254105
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Monitoring for Radar Bands Using Deep Convolutional Neural Networks

Abstract: In this paper, we present a spectrum monitoring framework for the detection of radar signals in spectrum sharing scenarios. The core of our framework is a deep convolutional neural network (CNN) model that enables Measurement Capable Devices (MCDs) to identify the presence of radar signals in the radio spectrum, even when these signals are overlapped with other sources of interference, such as commercial Long-Term Evolution (LTE) and Wireless Local Area Network (WLAN). We collected a large dataset of RF measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…One of the pioneers in the domain were the authors of [9], who demonstrated that CNNs trained on time domain IQ data significantly outperform traditional approaches for automatic modulation recognition based on expert features such as cyclic-moment based features, and conventional classifiers such as decision trees, k-NNs, SVMs, NN and Naive Bayes. Selim et al [10] propose to use amplitude and phase difference data to train CNN classifiers able to detect the presence of radar signals with high accuracy. Akeret at al.…”
Section: B Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the pioneers in the domain were the authors of [9], who demonstrated that CNNs trained on time domain IQ data significantly outperform traditional approaches for automatic modulation recognition based on expert features such as cyclic-moment based features, and conventional classifiers such as decision trees, k-NNs, SVMs, NN and Naive Bayes. Selim et al [10] propose to use amplitude and phase difference data to train CNN classifiers able to detect the presence of radar signals with high accuracy. Akeret at al.…”
Section: B Related Workmentioning
confidence: 99%
“…The first, is a real-valued equivalent of the raw complex temporal wireless signal inspired by the results in [9]. The second, is based on the amplitude and phase of the raw wireless signal, similar to the one used in the work of Selim et al [10] for identifying radar signals. The last is a frequency domain representation inspired by the work of Danev et al [28] which showed that frequency-based features outperform their timebased equivalents for wireless device identification.…”
Section: Wireless Signal Representationmentioning
confidence: 99%
“…Machine learning (ML) techniques have shown great promise in image and speech identification problems, and are steadily gaining traction in applications within the wireless domain. ORACLE is solely built on a convolutional neural network architecture that has not only seen success in the above areas, but has also been previously used for modulation [2] and protocol identification [3]. ORACLE adopts a stagewise approach towards achieving practical classification.…”
Section: B Machine Learning For Rf Fingerprinting In Oraclementioning
confidence: 99%
“…In [163], an SVM solution is developed to classify interference in wireless sensor networks (WSNs) from IEEE 802.11 signals and microwave ovens. A recent work [164] shows the use of DCNNs to classify radar signals using both spectrogram and amplitude-phase representations of the received signal. In [165], DCNN models are proposed to accomplish interference classification on two-dimensional time-frequency representations of the received signal to mitigate the effects of radio interference in cosmological data.…”
Section: Wireless Interference Classificationmentioning
confidence: 99%